The development of indigenous trade and markets in West Africa : studies presented and discussed at the Tenth International African Seminar at Fourah Bay College, Freetown, December 1969 - Meillassoux, Claude (London : Oxford University Press for the International African Institute, 1971)
The text incudes papers discussed at the Tenth International African Seminar, held at Fourah Bay College, Freetown, Sierra Leone, in 1969, illustrate and discuss the effects of internal economic and political conditions and of external relations on the development of trade and markets in West Africa, from the period of the slave trade down to the recent growth in production for overseas markets and rapidly expanding urban centres. Various aspects of local and regional trade and markets from the nineteenth century onwards are examined. Papers of current interest include: (1) Kinship and trade among the Kooroko (J.-L. Anselle); (2) cultural strategies in the organization of trading diasporas (A. Cohen); (3) market cycles and socio-political " space " (M. Piault); (4) two types of West African house trade (P. Hill); (5) West African market places: temporal periodicity and locational spacing (R. H. T. Smith); (6) periodic and daily markets in West Africa (B. W. Hodder); (7) French Colonial policy in relation to Senegal's trading class (1820-1960) (S. Amin); (8) the supply resoonse of retail trading services to urban population growth in Ghana (R. M. Lawson); (9) capitalism, capital markets, and competition in West African trade (M. P. Miracle). M. B
French or English with summaries in either language.
Include bibliography and index
kjo 16/01/2019
Loans
Keywords: Markets; Africa, West